â€œSCHWINGER-THEOREMâ€: ASCENDING PHOTONS IN EQUIVALENCE PRINCIPLE IMPLY GLOBALLY CONSTANT c IN GENERAL RELATIVITY - Rossler, Otto E. (European Scientific Journal, ESJ, 2014)
Nobel laureate Julian Schwinger in his 1986 book â€œEinsteinâ€™s Legacyâ€ cast a new light on the Einstein equivalence principle and, by implication, on general relativity. He demonstrated that the gravitationally redshifted photons arriving upstairs in gravity possess their lower frequency and energy on emission already, without this fact being locally manifest downstairs. Thus unlike a stone thrown, photons do not lose their kinetic energy on the way up. The consequences of this counterintuitive finding are far-reaching. In particular, the long-abandoned global constancy of the speed of light c gets resurrected. This fact rules out all globally expanding solutions to the Einstein equation. The same far-reaching cosmological finding is already implicit in the recently discovered fundamental field of cryodynamics, sister discipline to thermodynamics.